Performance Evaluation of Modified IRI2016 and Its Application to the 24 hr Ahead Forecast foF2 Mapping Over China. Issue 11 (27th October 2022) - Song, Qian; Ye, Qian; Zhang, Xiaoxin; Mao, Tian; Guo, Jianguang
Abstract: In this paper, we have modified the International Reference Ionosphere model 2016 (IRI2016) with the Global Navigation Satellite System total electron content data observation in China by adjusting the ionospheric index (IG12) for given location and time. The capability of the modified IRI2016 to reproduce the F2 layer critical frequency foF2 is validated for high/low solar activity conditions and disturbed geomagnetic conditions for the time period 2014–2017 over low‐latitude ionosonde station located at Sanya in China. The analysis shows that the modified IRI2016 better reproduced the variability of the observed foF2 versus time and seasons. Also, the modified IRI2016 foF2 prediction exhibits lower root mean square error and higher correlation coefficients ( R ) over different solar activity periods, and significantly reduces the average percentage deviations (△foF2(%)) under enhanced geomagnetic activity periods. Subsequently, the 24 hr ahead forecast foF2 map over China constructed by the combination of the modified IRI2016 and the eXtreme Gradient Boosting algorithm is presented for the first time. The promising performance of the modified IRI2016 indicates that this combination method may be an effective way to predict the ionospheric parameters, though further validations are needed in the future work. Key Points: The International Reference Ionosphere model 2016 (IRI2016) is modified with the Global Navigation Satellite System data by adjusting the ionospheric index for given location and time in China The modified IRI2016 improves the foF2 prediction for both high/low solar activity conditions and disturbed geomagnetic conditions The 24 hr ahead forecast foF2 map over China is constructed for the first time to our knowledge